Frequency and related factors of tubal patency after methotrexate treatment in women with ectopic pregnancy. Issue 3 (22nd December 2015) - Seyedoshohadaei, Fariba; Mohammadbeigi, Robabeh; Tahmuri, Atefe; Ghaderi, Ebrahim
Abstract: Aim: Ectopic pregnancy is a medical emergency. The classic treatment for this condition is surgery but early diagnosis allows for non‐surgical treatment. In recent years, intramuscular methotrexate has been considered, due to easy administration, its less invasive nature and low complications, but there are arguments about its effects. The aim of this study was to evaluate tubal patency after treatment of ectopic pregnancy with methotrexate and related factors. Methods: This cross‐sectional study was conducted on 80 women with ectopic pregnancy who were admitted to Sanandaj Be'sat Hospital in 2014. Patients who had successful treatment for ectopic pregnancy with single or multiple doses of methotrexate 50 mL/m 2 were enrolled. Three to 6 months after treatment, the patients were evaluated for tubal patency by hysterosalpingography. Data were analyzed usingspss, t ‐tests, χ 2 ‐test and logistic regression. Results: The tubal patency rate after treatment of ectopic pregnancy with methotrexate was 75% in hysterosalpingography. The average size of the ectopic pregnancy mass of women with open fallopian tubes was 22.5 ± 7.0 mm and for women with closed fallopian tubes it was 34.7 ± 10.0 mm ( P = 0.0001). β‐human chorionic gonadotropin levels were 642.1 ± 850.5 in women with open fallopian tubes and 3816.3 ± 4487.3 for women with closed fallopian tubes ( P = 0.0001). There was no significant correlation statistically between tubal patency with a history of stillbirth and number of pregnancies ( P > 0.5). There was a statistically significant relation between tubal patency and the number of births and also methotrexate dose ( P < 0.05). Conclusion: Treatment of ectopic pregnancy with methotrexate is effective for saving tubal patency. Levels of human chorionic gonadotrophin‐β < 1745, the treatment regimen of methotrexate (single or multiple doses) and ectopic pregnancy mass size smaller than 33.5 mm are significant predictors of tubal patency.